Video Transmission and Navigation System using QR-Code on Quadcopter - Saraswati, Shinta Dwiyana; yulianto, Ahmad Wilda; Zakaria, M. Nanak (Politeknik Negeri Malang, 2023)
In the current era of 4.0 technology, there are many quadcopter applications for testing and usability in life) to monitor the surrounding environment while operating and navigate through the GCS depending on the purpose made. Therefore, the operation of the drone is controlled directly by the operator through certain communication networks such as remote control or automatically through devices that have been previously programmed. This is necessary in order to make it easier to move the drone and monitoring can be done through operator directions or image processing. Image Processing in the form of a QR Code that can provide directions to the drone so that navigation can run smoothly. Research using how the camera detects QR Code will give directions to the drone to navigate to make movements following the QR Code directions in a sequence of numbers so that the final result in the form of video can be viewed via GCS and camera via IP CAM. The results of this study indicate that the drone can detect QR Code and opencv also successfully translates pixels is a distance of 5 meters and navigating based on pixel size with more than 100 pixels, the drone can move automatically to a certain destination. With a distance of 1 meter, it produces 100 pixels on the x-axis and 108 pixels on the y-axis, while for the furthest distance from the QR Code, which is 5 meters, it produces 50 pixels on the x-axis and 80 pixels on the y-axis.